Antimicrobial effectiveness of wound matrices containing native extracellular matrix with polyhexamethylene biguanide. Issue 1 (6th May 2021) - Davis, Stephen C.; Gil, Joel; Solis, Michael; Higa, Alexander; Mills, Allyson; Simms, Colin; Pena, Pilar Valencia; Li, Jie; Raut, Vivek
Abstract: A variety of wound matrix materials that are designed to help heal both acute and chronic wounds are currently available. Because wounds often encounter opportunistic microbes that can delay healing, the effectiveness of these materials is often suboptimal, resulting in delayed or compromised wound healing. The importance of reducing and controlling wound microbes is well recognised and there are several antimicrobial options available to address this unmet clinical need. This study compares the antimicrobial and wound healing capabilities, both in vivo and in vitro against methicillin‐resistant Staphylococcus aureus (MRSA) USA 300, for the following compounds: Collagen Wound Matrix‐Anti Microbial (CWM‐AM); Collagen Wound Matrix‐Anti Microbial XT (CWM‐AM XT); Antimicrobial Hydrofiber Wound Dressing (AHWD); Dermal Scaffold with Silver (DRSAg); Collagen Extracellular Matrix (CEM); Collagen Wound Matrix (CWM); Matrix Wound Dressing with Silver (MWDAg); Cadexomer Iodine Gel (CIG); Triple Antibiotic Ointment (TAO); and Antimicrobial Wound Gel (AWG). For the in vitro zone of inhibition assay, AWG and CIG had the largest diffused areas, followed by CWM‐AM and CWM‐AM XT. Furthermore, CWM‐AM, CWM‐AM XT, AWG, and CIG exhibited a persistent antimicrobial activity for up to 10 days after incubation. However, in the cytotoxicity studies performed using human fibroblasts, CWM‐AM and CWM‐AM XT had no detrimental effects in cell proliferation and viability, while AWG and CIG were cytotoxic and prohibitive for cell proliferation. Treatments were then assessed for microbiology and wound healing efficacy using an in vivo porcine deep reticular dermal wound model. CWM‐AM XT displayed the greatest in vivo antimicrobial activity against MRSA USA300 and expedited the reepithelialisation at a faster rate than other treatment groups. This study shows that a novel collagen matrix containing an antimicrobial agent can reduce the bacterial load and support healing.